Environmental impact assessment a guide to procedures. (Thomas Telford, 2000)
This guide explains how EC requirements for environmental impact assessment have been incorporated into procedures in the UK. It revises the booklet Environmental Assessment: A Guide to the Procedures, published in 1989, to take account of the requirements of the Directive 97/11/EC, which was adopted on 3 March 1997 and came into force on 14 March 1999.